2013
DOI: 10.1017/s143192761301266x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation Mechanism of Nickel Oxide/Carbon Nanotube Composite

Abstract: Abstract:The oxidation mechanism and thermal stability of nickel oxide~NiO!/carbon nanotube~CNT! composites were investigated by examining composites with different NiO contents by thermogravimetric analysis and transmission electron microscopy~TEM!. NiO acts as a catalyst in the oxidation of CNT in the composite. CNTs can be oxidized, even in a vacuum, by reducing NiO to nickel at temperatures lower than the normal oxidation temperature of CNTs. This phase transition was confirmed directly by in situ heating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…It was reported that O ads on the surface of the catalyst is favorable for reduction and oxidation processes. 39 Two characteristic peaks appeared in the Ca 2p spectrum (Fig. 3d), which belonged to calcium oxide (∼346.5 eV) and residual carbonate (∼350.5 eV).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…It was reported that O ads on the surface of the catalyst is favorable for reduction and oxidation processes. 39 Two characteristic peaks appeared in the Ca 2p spectrum (Fig. 3d), which belonged to calcium oxide (∼346.5 eV) and residual carbonate (∼350.5 eV).…”
Section: Resultsmentioning
confidence: 97%
“…3a). 39 Two characteristic peaks appeared in the Ca 2p spectrum (Fig. 3d), which belonged to calcium oxide (∼346.5 eV) and residual carbonate (∼350.5 eV).…”
Section: Co 2 Capture and Methanation Performance Over The Ni/ Cao/γ-...mentioning
confidence: 97%
“…Above 650°C, the oxidation rate is more dependent of thickness of oxygen gas film over the material surface, which is thicker as higher the gas pressure. The oxidation mechanisms of carbon phase have rate-controlled steps at temperatures ranging between 400 and 800°C and depend on activation energies originated from different composite morphologies [13][14].…”
Section: Introductionmentioning
confidence: 99%